Imaging the gods: animal mummies from Tomb 3508, North Saqqara, Egypt. (18th February 2019) - Atherton-Woolham, Stephanie; McKnight, Lidija; Price, Campbell; Adams, Judith
Abstract: Abstract : A collection of mummified animals discovered in 1964 in a Third Dynasty mastaba tomb at North Saqqara, Egypt, offers the unusual and unique opportunity to study a group of mummies from a discrete ancient Egyptian context. Macroscopic and radiographic analyses of 16 mummy bundles allow parallels to be drawn between the nature of their internal contents and their external decoration. The evidence suggests that incomplete and skeletonised animal remains fulfilled the equivalent votive function as complete, mummified remains, and that a centralised industry may have produced votive mummies for deposition at the Saqqara Necropolis.